Practical application of failure criteria in determining safe mud weight windows in drilling operations - Gholami, Raoof; Moradzadeh, A.; Rasouli, V.; Hanachi, J. (2014)
Wellbore instability is reported frequently as one of the most significant incidents during drilling operations. Analysis of wellbore instability includes estimation of formation mechanical properties and the state of in situ stresses. In this analysis, the only controllable parameter during drilling operation is the mud weight. If the mud weight is larger than anticipated, the mud will invade into the formation, causing tensile failure of the formation. On the other hand, a lower mud weight can result in shear failures of rock, which is known as borehole breakouts. To predict the potential for failures around the wellbore during drilling, one should use a failure criterion to compare the rock strength against induced tangential stresses around the wellbore at a given mud pressure. The Mohr-Coulomb failure criterion is one of the commonly accepted criteria for estimation of rock strength at a given state of stress. However, the use of other criteria has been debated in the literature. In this paper, Mohr-Coulomb, Hoek-Brown and Mogi-Coulomb failure criteria were used to estimate the potential rock failure around a wellbore located in an onshore field of Iran. The log based analysis was used to estimate rock mechanical properties of formations and state of stresses. The results indicated that amongst different failure criteria, the Mohr-Coulomb criterion underestimates the highest mud pressure required to avoid breakouts around the wellbore. It also predicts a lower fracture gradient pressure. In addition, it was found that the results obtained from Mogi-Coulomb criterion yield a better comparison with breakouts observed from the caliper logs than that of Hoek-Brown criterion. It was concluded that the Mogi-Coulomb criterion is a better failure criterion as it considers the effect of the intermediate principal stress component in the failure analysis. © 2013 Institute of Rock and Soil Mechanics, Chinese Academy of Sciences.